Study on etiology, risk factors, severity and outcome of newborns presenting with respiratory distress in neonatal intensive care unit - Fatima, Syeda Asra; Thobbi, Achyut Narayanrao (International Journal of Contemporary Pediatrics, 2024)
Background: Respiratory distress (RD) is one of the frequent complications in neonates within 24 hours of delivery. Early recognition and treatment are important to prevent morbidity and mortality. The aim of the study was to assess the etiology, risk factors and outcome of neonates with RD. Methods: This was a prospective study conducted on 75 newborns admitted to neonatal intensive care unit (NICU) of tertiary healthcare center. The severity of the RD was assessed using Silverman-Anderson (SA) and Downes scoring clinical scoring and the final outcome of neonates were evaluated. Results: The incidence of RD was higher in male newborns (69.3%), caesarian section delivery (68%) and the onset of RD was 24 hours in 74.7% of the neonates. SA and Downe’s scoring showed moderate severity in 61.3% of the neonates. The major etiology was transient tachypnea of newborn (TTN) and RD syndrome (RDS) in 40% and 24% of the neonates respectively. The preferred treatment modality was oxygen support in 58.7% and mortality rate in this study was 4%. Conclusions: The common etiology of RD was TTN and the important risk factors include male gender, caesarian section delivery and preterm delivery.